Ideologies of Motherhood: Meaning Making and Decision Making around Paid Work in a West Ryde Playgroup. (28th October 2015) - Stockey‐Bridge, M.
Abstract: Paid work or full‐time at‐home caring? That is the question facing many Australian middle‐class mothers today. A growing body of research and literature compares Western middle‐class mothers who work for money with those that work as "full‐time" carers of their children. Or alternatively, research concerns have centered on the sociological, cultural, and psychological impact that either decision may have on children, the mother, and/or the nation. This article aimed to reverse the trend of comparing mothers or concerning ourselves with children; instead, I examine the impact of social expectations and ideologies on the decisions mothers make, and how this affects their agency.